Oxotitanium (IV) Complexes with 4-Salicylideneamino-3,5-dimercapto-1,24-triazoles - Shivaprasad, K.H.; Angadi, S.D.; Kulkarni, V.H.; Patil, B.R. (Asian Journal of Chemistry, 2010)
Oxotitanium(IV) complexes have been prepared by reacting oxotitanium(IV) perchlorate with salicylideneamino-3,5-dimercapto- 1,2,4-triazoles in ethanol medium. The complexes are orange yellow in colour. These complexes have been characterised by elemental analysis and spectral data Five-coordinated trigonal bipyramidal structure has been proposed for these complexes.